Application of latent semantic indexing on Malay-English cross language information retrieval - Abdullah, Muhamad Taufik; Ahmad, Fatimah; Mahmod, Ramlan; Sembok, Tengku Mohd Tengku (Springer Berlin Heidelberg, 2003)
This paper concerns an application of latent semantic indexing on Malay and English cross language information retrieval system. The retrieval effectiveness was tested on the actual Quranic collection using latent semantic indexing model. The results show that average precision on cross language is higher than monolingual retrieval.